1998
DOI: 10.1007/bf02783151
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of infertility rates in communities from boron-rich and boron-poor territories

Abstract: As a part of a large-scale work aimed at studying the health effects of boron (B) in residents of a country with the world's largest supply, developmental effects of B are presented. Spontaneous abortions, stillbirths, and congenital malformations in addition to early infant mortality were questioned in the field by home visits. Although the number of families so far ascertained is rather small, the rates related to spontaneous abortions and stillbirths from high B exposure vs low B exposure subpopulations rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Of even greater concern is the fact that the rationale for the current regulations is subject to question due to scientific uncertainty. It is imperative that discussions and policies developed are based on sound science [8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Of even greater concern is the fact that the rationale for the current regulations is subject to question due to scientific uncertainty. It is imperative that discussions and policies developed are based on sound science [8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Initially, reproduction toxicology studies were based upon data obtained from animal studies and adapted to human risk evaluations 20 . It was reported in several field studies that B does not affect human reproductive systems or the sexual capabilities of people exposed to daily high levels 21 – 25 . Although these aforementioned field studies were performed in B-rich areas, the average daily B exposure in the field was not determined at that time.…”
mentioning
confidence: 99%
“…A first series of studies into human reproductive toxicity has been performed in environmentally exposed populations residing in boron-rich areas of Turkey with high drinking water levels and no clear-cut effects on reproduction were observed (Şaylı et al 1998;Korkmaz et al 2007). Also, fertility figures Şaylı et al 1998;Korkmaz et al 2011) and spontaneous abortions and stillbirths (Tüccar et al 1998) showed no difference between subpopulations with high vs. low boron exposure.…”
Section: Studies In Turkeymentioning
confidence: 91%